Pengaruh Penguasaan Konsep SPtLDV Terhadap Kemampuan Menyelesaikan Soal-Soal Program Linear Kelas XI MIA SMAN 3 Baubau - Herlawan Herlawan; Wa Ode Novri Liyanti (Jurnal Akademik Pendidikan Matematika, 2021)
This research aimed to determine the influence of mastery SPtLDV the ability to solve linear program questions for grade XI MIA SMAN 3 Baubau.This research was a quantitative research using ex-post facto method with simple regression analysis technique. Population in this research were 64 students of class XI MIA SMAN 3 Baubau in academic year 2020/2021. The sample in this research, the sampling technique used was the Cluster Random Sampling technique. Data collection was carried out by providing research instruments (test) to respondents to neasure students’ mastery of SPtLDV material in solving linear program questions. The results of the research were then analyzed using descriptive analysis and inferential analysis in the form of t-test. Based the results of analysis, it concluded that: 1)mastery of SPtLDV concept of grade XI MIA SMAN 3 Baubau obtained average value 50.85,percentage of 65%, this showed value in high category, namely 13 of 20 students. 2)The level of students’ ability in solving the linear program questions of XI MIA SMAN 3 Baubau obtained an average value 53.20,percentage of 65%, this showed value in high category, namely 13 of 20 students, and 3)based on the results of simple linear regression analysis, it is obtained tcount(t0)=4.666 and ttable=2,101. It meant is tcount>ttable (4.666>2.101),then and H0 was rejected and H1 was accepted, so that it was conclude that: there was effect of mastery SPtLDV concept on the ability to solve linear program questions for grade XI MIA SMAN 3 Baubau by 54.7% while 45.3% influenced by other variables not included in this research.